Implementing Pancasila Values in Facing Technological Developments and Digitalization in the Era of Society 5.0 - Samosir, Hairul Amren; Simanungkalit, Adolf Valentino; Ramadhan, Bagas Anugerah; Amin, Fauzi Ihsan; Taufan, Anugerah Muthia (LPPM UIKA Bogor, 2024)
The Society 5.0 era, which integrates advanced technology into everyday life, brings new challenges and opportunities for Indonesia. All values become the moral foundation in facing this transformation. The implementation of Pancasila in the Society 5.0 era teaches that technology must support all human values and social justice, strengthen unity, and be used for shared prosperity. Education plays an important role in forming students' independent character and integrity, while nationalism and diversity of beliefs help maintain social cohesion. Technology, if used responsibly, can improve the quality of life through increased access to information and education, as well as health services. Real examples of this implementation can be seen in online education programs and health applications which are based on all Pancasila values, ensuring that technological progress brings equitable and sustainable benefits to all Indonesian society. Era Society 5.0 also invites Indonesia to adopt technology with Pancasila values as a moral guide. Through education that prioritizes character and diversity united by nationalism, Indonesia can face global challenges in a way that promotes social justice and shared prosperity. This research aims to implement the values of the Pancasila principles in the application of technological developments and digitalization which continue to grow rapidly, so that the younger generation is able to apply their abilities to existing developments in a positive and targeted manner. This research was based on qualitative methods that have been carried out with positive results during socialization within the dormitory. Responsible implementation of technology, such as in online education and health applications, is a concrete example of how these values can be realized to improve the lives of all citizens in an inclusive and sustainable way.